Two-dimensional MoS2-melamine hybrid nanostructures for enhanced catalytic hydrogen evolution reaction - Kwak, In Hye; Kwon, Ik Seon; Debela, Tekalign Terfa; Seo, Jaemin; Ahn, Jae-Pyoung; Yoo, Seung Jo; Kim, Jin-Gyu; Park, Jeunghee; Kang, Hong Seok (ROYAL SOC CHEMISTRY, 2019)
Two-dimensional (2D) MoS2 nanostructures have attracted much attention in recent years because of their excellent electrocatalytic activity toward the hydrogen evolution reaction (HER). Herein, we report unique 2D hybrid nanostructures of MoS2 and melamine synthesized via a one-step solvothermal process. Remarkably, few-layer metallic 1T ' phase MoS2 nanoflakes and orthorhombic phase melamine aggregate to form nanoplates. At a controlled concentration, the melamine molecules intercalated into the 1T ' phase MoS2 by forming charge-transfer complexes. The hybrid complexes with 7% intercalated melamine exhibited excellent performance for the catalytic HER, with a current of 10 mA cm(-2) at 0.136 V (vs. RHE) and a Tafel slope of 37 mV dec(-1). First-principles calculations showed that the intercalation of hydrogen-bonded melamine clusters could stabilize the 1T ' phase MoS(2)via substantial charge transfer. The activation barrier was calculated for the Volmer-Heyrovsky reactions, by identifying the active sites of the Volmer reaction as the basal S atoms above the hydrogen-bonded amine group of melamine. This rationalizes the dependence of the catalytic activity on the concentration of intercalated melamine. The present study highlights the opportunities for producing unique 2D hybrid complexes to enhance the HER catalytic activity by controlling the intercalating organic molecules.